The use of "Kartun Anak" YouTube channel in supporting students' speaking skill - Zahratunnisa' Aulia; Yuliati (ELT Forum: Journal of English Language Teaching, 2025)
YouTube is a platform that provides audiovisual media that can be used for teaching and learning activities. Audiovisual can be used for teaching language skills, including speaking skills. In this research, the author discussed the use of YouTube videos in the class, focusing on students’ English speaking skills. Observations and interviews were conducted to gain data regarding the use of YouTube in supporting students’ speaking skills. Two teachers and ten students were interviewed to gain deeper information. The author discovered that the teachers chose the videos based on the chapter and materials that were going to be taught, and the YouTube channel provides suitable materials. The students were way more enthusiastic during the class using audiovisual media compared to any class without audiovisual media. When asked about the media, the students stated that the animations were appealing and they gain new vocabulary through the use of the media, which made them gain interests in learning new vocabulary and how to pronounce words correctly. According to the teachers, changes in students’ speaking skill appeared during the class. Students often struggled with pronunciation and they showed improvements when this media was used in the class. They stated that the clear pronunciations from the videos helped the students to learn the accurate pronunciations.